Qualidade de vida de idosos institucionalizados - Freitas, Mariana Ayres Vilhena De [UNESP] (2010)
INTRODUCTION: as the population ages increases, the search for institutions for elderly and Brazil is not structurally prepared to meet this demand. Institutionalization can bring countless consequences, because every change implies either positive or negative factors. OBJECTIVES: to evaluate and to compare the quality of life (QL) in institutionalized elderly. METHODS: 36 institutionalized seniors of the city of Avaré, SP, participated in the research of three institutions, forming three groups. The questionnaire used was the SF 36, to evaluate the quality of life. RESULTS: the domain General of Health obtained similar values for the three long term care institutions, however with a low score (22). The score Emotional Aspects was significantly different from the other long term care (p < 0,01). The results of the study point that that the quality of life of institutionalized seniors of city of Avaré is low, showing the importance of the evaluation of QL in those institutions.